Facets of the problem of infiltrative endometriosis: from pathogenesis to effective therapy - Viktor E. Radzinskii; Mekan R. Orazov; Ljudmila M. Mihaleva; Madina A. Bekulova (Гинекология, 2021)
Endometriosis remains an unresolved problem in gynecology. The urgency of the fight against this disease is due to its high prevalence among women of reproductive age. Endometriosis, especially its infiltration forms, affects all aspects of the patients life, its clinical manifestations pelvic pain, dyspareunia, dysmenorrhea, dyschezia, lead to social disadaptation, problems in personal life, depression and anxiety. The socio-economic burden of the disease motivates researchers to further study the pathogenesis of endometriosis and search for pathogenetically justified pharmacological solutions.